2011
DOI: 10.4161/cc.10.12.16002
|View full text |Cite
|
Sign up to set email alerts
|

Matrix remodeling stimulates stromal autophagy, “fueling” cancer cell mitochondrial metabolism and metastasis

Abstract: We have previously demonstrated that loss of stromal caveolin-1 (Cav-1) in cancer-associated fibroblasts is a strong and independent predictor of poor clinical outcome in human breast cancer patients. However, the signaling mechanism(s) by which Cav-1 downregulation leads to this tumor-promoting microenvironment are not well understood. To address this issue, we performed an unbiased comparative proteomic analysis of wild-type (WT) and Cav-1(-/-) null mammary stromal fibroblasts (MSFs). Our results show that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 56 publications
(86 reference statements)
0
37
0
Order By: Relevance
“…Other proteins also contribute to apoptosis resistance in this tumor model. Castello-Cros et al (2011) reported that the stromal fibroblasts lacking Cav-1 significantly increased plasminogen activator inhibitor type 1 and type 2 (PAI-1 and PAI-2) expression and that in xenografts, co-inoculation with fibroblasts that stably express either PAI-1 or PAI-2 significantly reduced the extent of apoptosis of MDA-MB-231 human breast tumors. Finally, we cannot rule out the possibility that Hsp70 is also playing another role apart from the suppression of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Other proteins also contribute to apoptosis resistance in this tumor model. Castello-Cros et al (2011) reported that the stromal fibroblasts lacking Cav-1 significantly increased plasminogen activator inhibitor type 1 and type 2 (PAI-1 and PAI-2) expression and that in xenografts, co-inoculation with fibroblasts that stably express either PAI-1 or PAI-2 significantly reduced the extent of apoptosis of MDA-MB-231 human breast tumors. Finally, we cannot rule out the possibility that Hsp70 is also playing another role apart from the suppression of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Most interesting, SERPINB2 (Plasminogen Activator Inhibitor 2) functions as a tumor suppressor, when expressed by cancer cells (49) but becomes a clear-cut oncogene if expressed by fibroblasts. In breast cancer models, it contributes to the formation of autophagic stroma, which fuels mitochondrial metabolism in cancer cells and promotes metastasis (50) or enables cancer cell survival and vascular cooption in the brain (51). …”
Section: Discussionmentioning
confidence: 99%
“…175 Indeed, the increased glycolysis due to enhanced mitochondrial turnover generates excessive stromal cell lactate and ketones, which are secreted into the intracellular space. 176 The cancer cells then take up the high-energy metabolites (lactate and ketones) and use them to feed cancer cell mitochondrial energy production and generate mitochondrial precursors for the biogenesis of new cancer cells. Lactate and ketones from the autophagic tumor stroma increase the transcriptional expression of gene profiles normally associated with stemness, including genes commonly upregulated in embryonic stem cells, and may therefore promote the dynamic appearance of CSC cellular states, resulting in significant decreases in patient survival.…”
Section: Autophagy In Cancer Stem Cellsmentioning
confidence: 99%